Advancing energy systems with in-situ and operando surface-enhanced Raman scattering spectroscopy - Bao, Haoming (2024)
Surface-enhanced Raman scattering spectroscopy (SERS) has emerged as a powerful analytical technique to enable nanoscale investigations of energy systems. This mini-review focuses on the applications of in-situ and operando SERS in energy-related research, highlighting its unique capabilities and significant contributions to understanding energy storage and conversion processes. We first introduce the fundamental principles of SERS, key SERS-derived techniques, and commonly employed platforms. Subsequently, we delve into the diverse applications of in-situ and operando SERS across various energy systems, encompassing photocatalytic and electrocatalytic systems, fuel cells, solar cells, and batteries. Finally, we conclude with our perspective on the current challenges and prospects in this area. We hope this mini-review serves as an essential overview to guide the design and implementation of in-situ and operando SERS studies of energy systems.